Multimode Transmission in Network MIMO Downlink with Incomplete CSI. (19th October 2010) - Seifi, Nima; Viberg, Mats; Heath, Robert W.; Zhang, Jun; Coldrey, Mikael
Abstract : We consider a cooperative multicell MIMO (a.k.a network MIMO ) downlink system with multiantenna base stations (BSs), which are connected to a central unit and communicate with multiantenna users. In such a network, obtaining perfect channel state information (CSI) of all users at the central unit to exploit opportunistic scheduling requires a substantial amount of feedback and backhaul signaling. We propose a scheduling algorithm based only on the knowledge of the average SNR at each user from all the cooperating BSs, denoted as incomplete CSI. Multimode transmission is applied that is able to adaptively adjust the number of data streams transmitted to each user. Utilizing the results of random matrix theory, an analytical framework is proposed to approximate the ergodic rate of each user with different number of data streams. Using these ergodic rates, a joint user and mode selection algorithm is proposed, where only the scheduled users need to feed back instantaneous CSI. Simulation results demonstrate that the developed analytical framework provides a good approximation for a practical number of antennas. While substantially reducing the feedback overhead, it is shown that the proposed scheduling algorithm performs closely to the opportunistic scheduling algorithm that requires instantaneous CSI feedback from all users.